Structural monitoring of ARTistic and historical BUILding testimonies : selected, peer reviewed papers from the Final International Conference SMART BUILT 2014, March 27-29, 2014, Bari, Italy - Foti, Dora, 1962- (Key engineering materials ;, 2014)
Collection of selected, peer reviewed papers from the Final International Conference SMART BUILT 2014, March 27-29, 2014, Bari, Italy. The 36 papers are grouped as follows: Chapter 1: Historical and Artistic Area, Chapter 2: Structural Area, Chapter 3: Computational and Technological Area.